2005
DOI: 10.1634/stemcells.2004-0162
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Human and Murine ESCs Identifies Divergent Paths Required to Maintain the Stem Cell State

Abstract: Human embryonic stem cells (hESCs) are an important source of stem cells in regenerative medicine, and much remains unknown about their molecular characteristics. To develop a detailed genomic profile of ESC lines in two different species, we compared transcriptomes of one murine and two different hESC lines by massively parallel signature sequencing (MPSS). Over 2 million signature tags from each line and their differentiating embryoid bodies were sequenced. Major differences and conserved similarities betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
177
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(198 citation statements)
references
References 54 publications
14
177
2
3
Order By: Relevance
“…Previous studies have reported tissue-specific TAF variants and alterations in TAF expression (reviewed in D'Alessio et al, 2009; Müller et al, 2010), but the composition of hESC TAFs is unprecedented and is likely highly specific, if not unique, to hESCs. For example, we find that mouse ESCs, which bear both similarities and differences to hESCs (Ginis et al, 2004; Wei et al, 2005; Schnerch et al, 2010), express all TFIID TAFs analyzed (Figure 9), consistent with the results of a recent study that focused on the role of TAF3 in mouse ESCs (Liu et al, 2011).
10.7554/eLife.00068.024Figure 9.TAF expression in mouse ESCs.Immunoblot analysis monitoring TAF levels in PGK12.1 mouse ESCs and, as a control, HeLa cells.
…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported tissue-specific TAF variants and alterations in TAF expression (reviewed in D'Alessio et al, 2009; Müller et al, 2010), but the composition of hESC TAFs is unprecedented and is likely highly specific, if not unique, to hESCs. For example, we find that mouse ESCs, which bear both similarities and differences to hESCs (Ginis et al, 2004; Wei et al, 2005; Schnerch et al, 2010), express all TFIID TAFs analyzed (Figure 9), consistent with the results of a recent study that focused on the role of TAF3 in mouse ESCs (Liu et al, 2011).
10.7554/eLife.00068.024Figure 9.TAF expression in mouse ESCs.Immunoblot analysis monitoring TAF levels in PGK12.1 mouse ESCs and, as a control, HeLa cells.
…”
Section: Discussionsupporting
confidence: 90%
“…hESCs are also similar in their ability to proliferate and differentiate into cell types of the three germ layers in vitro and in vivo [9 -16]. Properties of hESCs have also been compared using microarray, expressed sequence tag (EST) scan, serial analysis of gene expression (SAGE), and massively parallel signature sequencing (MPSS) [4,[17][18][19][20][21][22][23][24][25][26][27]. These studies suggest that it is likely that markers shared by hESC lines, but absent in other cell populations, exist.…”
Section: Introductionmentioning
confidence: 99%
“…The unique proliferative properties of human ES cells may be related to a naïve transcriptome which is dedicated to self-propagation through mitotic cell division and sustenance of a pluripotent uncommitted state (Thomson et al, 1998;Amit et al, 2000;Pera et al, 2000;Bhattacharya et al, 2004;Brandenberger et al, 2004;Miura et al, 2004;Rao et al, 2004;Boyer et al, 2005;Wei et al, 2005). Defining the molecular basis of pluripotency and the capability of human ES cells for self renewal is critical for the rational design of biomedical applications of human ES cells as a cellular source for tissue replacement (Carpenter et al, 2003;Sato et al, 2003;Heins et al, 2004;Stojkovic et al, 2004;Zwaka and Thomson, 2005).…”
mentioning
confidence: 99%